2018
DOI: 10.1074/jbc.ra118.004242
|View full text |Cite
|
Sign up to set email alerts
|

The lateral meningocele syndrome mutation causes marked osteopenia in mice

Abstract: Lateral meningocele syndrome (LMS) is a rare genetic disorder characterized by neurological complications and osteoporosis. LMS is associated with mutations in exon 33 of NOTCH3 leading to a truncated protein lacking sequences for NOTCH3 degradation and presumably causing NOTCH3 gain-of-function. To create a mouse model reproducing human LMS-associated mutations, we utilized CRISPR/Cas9 to introduce a tandem termination codon at bases 6691-6696 (ACCAAG>TAATGA) and verified this mutation (Notch3 tm1.1Ecan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 81 publications
(58 reference statements)
6
52
0
Order By: Relevance
“…Total RNA was extracted from cells with the RNeasy kit (Qiagen, Valencia, CA) in accordance with manufacturer's instructions (Canalis et al, 2016; Canalis et al, 2018; Nazarenko, Lowe et al, 2002; Nazarenko, Pires, Lowe, Obaidy, & Rashtchian, 2002). Equal amounts of RNA were reverse‐transcribed using the iScript RT‐PCR kit (BioRad, Carlsbad, CA) and amplified in the presence of specific primers (all primers from Integrated DNA Technologies, Coralville, IA; Table 1) with the iQ SYBR Green Supermix or SsoAdvanced TM Universal SYBR Green Supermix (BioRad) at 60°C for 40 cycles.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from cells with the RNeasy kit (Qiagen, Valencia, CA) in accordance with manufacturer's instructions (Canalis et al, 2016; Canalis et al, 2018; Nazarenko, Lowe et al, 2002; Nazarenko, Pires, Lowe, Obaidy, & Rashtchian, 2002). Equal amounts of RNA were reverse‐transcribed using the iScript RT‐PCR kit (BioRad, Carlsbad, CA) and amplified in the presence of specific primers (all primers from Integrated DNA Technologies, Coralville, IA; Table 1) with the iQ SYBR Green Supermix or SsoAdvanced TM Universal SYBR Green Supermix (BioRad) at 60°C for 40 cycles.…”
Section: Methodsmentioning
confidence: 99%
“…One group created a human lateral meningocele syndrome (LMS)-related mutant mouse model of the Notch3 gene via microinjection of the Cas9 mRNA and gRNA. The LMS-related mutant mouse model induced a 35%-60% decrease in the cancellous bone volume, together with a reduction in trabecular number, which mimics the skeletal manifestation of lateral meningocele syndrome (Canalis et al 2018). In addition, several studies have reported mouse models of osteoporosis that were generated by knocking out the ATP6V1H gene, a subunit of V- Figure 1.…”
Section: Mice and Ratsmentioning
confidence: 99%
“…Expectedly, CRISPR/Cas9 gene editing in these mouse and zebrafish models of human skeletal disease has swiftly evolved as comprehensively reviewed, by Wu et al ( 189 ). To date, CRISPR/Cas9 models have been done for several skeletal disorders such as OI ( 190 ), meningocele syndrome ( 191 ) and campomelic dysplasia ( 192 ). OI type V is a rare autosomal dominant disease characterized by increased bone fragility, low BMD and increased susceptibility to bone fracture followed by hyperplastic callus formation.…”
Section: Current Progress In Gene Editing For Monogenic and Complex Bmentioning
confidence: 99%